Competition for impurity atoms between defects and solid solution during high pressure torsion. (December 2019) - Mazilkin, A.A.; Straumal, B.B.; Kilmametov, A.R.; Boll, T.; Baretzky, B.; Kogtenkova, O.A.; Korneva, A.; Zięba, P.
Abstract: During high-pressure torsion (HPT) the dynamic equilibrium establishes with a certain steady-state composition of the solid solution along with the grain refinement by a factor of more than thousand. The formation of such HPT steady-state in copper alloys with Co, Ag and In has been studied. If precipitates of a second phase were present in the sample before HPT, their dissolution led to the enrichment in the (Cu) matrix solid solution. If precipitates of a second phase were absent, the HPT led to the depletion in the (Cu) matrix due to the segregation in newly formed defects like grain boundaries. Graphical abstract: Unlabelled Image